Antibacterial Activity of Textiles for Wound Treatment. Issue 5 (September 2015) - Pinho, Eva; Soares, Graça; Henriques, Mariana; Grootveld, Martin
Major advances in the development and use of antimicrobial textiles to control bacterial proliferation on wound beds continue. However, wound dressings are, in general, not included in standardized regimens for measuring and monitoring their antimicrobial effectiveness. This work adapts these methods to assess the antibacterial activity of textiles designed for wound healing purposes. Environmental conditions representative of those present at the wound site (i.e., moisture levels, infection, and available nutrients) were evaluated. This work shows that moisture levels were the environmental factor that had the greatest influence on the antimicrobial agent activities tested. These results suggest that it is possible to use the more representative environmental conditions present on the wound bed for in vitro screening of textile antimicrobial activity.